Description of a new species of Bush frog (Anura: Rhacophoridae: Raorchestes) from northwestern Yunnan, China - Wu, Yun-He; Liu, Xiao-Long; Gao, Wei; Wang, Yu-Fan; Li, Ying-Chun; Zhou, Wei-Wei; Yuan, Zhi-Yong; Che, Jing (Zootaxa, 2021)
Approximately half of the species in speciose genus Raorchestes were described during the past 10 years, yet only 11 species are known from Southeast Asia and southern China (SEA-SC), adjacent Himalayas, and northeastern India. Field work in northwestern Yunnan province, China resulted in the discovery of one new species in the genus based on morphological and molecular analyses. The new species is diagnosed by small size with 15.0–19.0 mm SVL in adult males (n=3); tongue pyriform, notched posteriorly; rudimentary webbing between toes; fingers and toes with narrow lateral dermal fringes; tibiotarsal articulation reaching anterior of the eye when hindlimb is stretched along the side of the body; relative finger lengths: I < II < IV < III, relative toe lengths: I < II < V < III < IV; inner metatarsal tubercle oval, outer metatarsal tubercle absent; finger discs and toe discs greyish or orange; flank near the crotch with a distinct black region between two creamy white patches, and the thigh having a similar black patch near the groin, proximal to another creamy white patch; a distinct “) (”-shaped dark marking on the back; male with external single subgular vocal sac; nuptial pad absent. A phylogenetic tree was reconstructed based on the mitochondrial genes for 16S rRNA and ND1. The results indicated that these individuals form a monophyletic group, and show high genetic divergence to their closest relatives within the genus (uncorrected p-distances > 3.2%) by distance of 16S comparable to the divergence between recognized Raorchestes species. This study further enriches the diversity of rhacophorids, especially in northwestern Yunnan.